Perbedaan Stress Kerja Antara Perawat UGD dan Ruang Rawat Inap di RSUD Dr. H. Abdul Moeloek Provinsi Lampung pada Masa pandemi Covid 19 - Sandi Esa Prayoga; Andoko Andoko; Usastiawaty Cik Ayu Saadiah Isnainy (Universitas Malahayati Lampung, 2023)
ABSTRACT Based on the results of the pre-survey at RSUD Dr. H. Abdul Moeloek by conducting free interviews with 20 nurses who were divided into 10 emergency room nurses and 10 inpatient room nurses. It was found that nurses said that when patients came to the Hospital (IGD), they felt very anxious, afraid, stressed, panicked, confused, worried, sad, and emotional when receiving patients suspected of having COVID, supported by the stigma of the Indonesian people who felt unsupportive, thus making psychologically disturbed nurses. News of the death of a doctor and nurse colleague also caused its own tension. Anxiety increases with inadequate PPE and has an impact on the transmission of medical personnel. To find out the difference in work stress between emergency room nurses and inpatient rooms in hospitals. DR. H. Abdul Moeloek Lampung Province During the Covid19 Pandemic Period in 2022 This type of research uses quantitative, the research design uses an analytical survey, with a cross sectional approach. The population and sample are nurses at RSUD Dr. H. Abdul Moeloek. The sampling technique used purposive sampling. Analysis of univariate and bivariate data using the Mann-Whitney U Test. The average stress of emergency room nurses in hospitals. DR. H. Abdul Moeloek Lampung Province During the Covid 19 Pandemic Period in 2022, with a mean of 62.92 a minimum score of 47 and a maximum score of 78. The average stress of inpatient nurses in hospitals. DR. H. Abdul Moeloek Lampung Province During the Covid 19 Pandemic Period in 2022, with a mean of 37.86 a minimum score of 14 and a maximum score of 64. The results of bivariate data analysis using an independent t-test obtained a p-value of 0.000 0.05, so it can be concluded it can be concluded that there is a difference in work stress between emergency room nurses and inpatient rooms in hospitals. DR. H. Abdul Moeloek Lampung Province During the Covid19 Pandemic Period in 2022. It is hoped that all nurses, especially in the emergency unit room, will always comply with the Health protocol in preventing the transmission of Covid-19, namely by consuming vitamins and health supplements. Keywords: Work Stress Between Emergency Room Nurses and Inpatient Rooms ABSTRAK Berdasarkan hasil pra survey di RSUD Dr. H. Abdul Moeloek dengan melakukan wawancara bebas kepada 20 perawat yang terbagi dalam 10 perawat ruang UGD dan 10 perawat ruang rawat inap. Didapat perawat mengatakan ketika pasien datang di Rumah Sakit (IGD), mereka merasa sangat cemas, takut, stress, panik, bingung, kawatir, sedih, dan emosi saat menerima pasien yang dicurigai covid, ditunjang dengan stigma masyarakat Indonesia yang dirasa tidak mendukung sehingga membuat psikologis perawat terganggu.Berita kematianteman sejawat dokter danperawatjuga mengakibatkan ketegangantersendiri. Diketahui perbedaan stress kerja antara perawat UGD Dan Ruang Rawat Inap di RSUD. DR. H. Abdul Moeloek Provinsi Lampung Pada Masa Pandemi Covid19 Tahun 2022. Jenis penelitian menggunakan kuantitatif, rancangan penelitian menggunakan survey analitik, dengan pendekatan cross sectional. Populasi dan sampel adalah perawat di RSUD Dr. H. Aabdul Moeloek. Teknik sampling menggunakan purposive sampling. Analisa data univariat dan bivariat menggunakan Uji Mann- Whitney U Test. Rata-rata stress perawat UGD di RSUD. DR. H. Abdul Moeloek Provinsi Lampung Pada Masa Pandemi Covid 19 Tahun 2022, dengan mean 62,92 nilai minimal skor 47 dan maksimal skor 78. Rata-rata stress perawat ruang rawat inap di RSUD. DR. H. Abdul Moeloek Provinsi Lampung Pada Masa Pandemi Covid 19 Tahun 2022, dengan mean 37,86 nilai minimal skor 14 dan maksimal skor 64. Hasil analisa data bivariat menggunakan uji t- tes independen didapat nilai p-value 0,000 0,05 maka dapat ditarik kesimpulan bahwa terdapat perbedaan stress kerja antara perawat UGD Dan Ruang Rawat Inap di RSUD. DR. H. Abdul Moeloek Provinsi Lampung Pada Masa Pandemi Covid19 Tahun 2022. Diharapkan kepada seluruh perawat khsusnya di ruang unit gaeat darurat agar selalu patuh terhadap protokol Kesehatan dalam pencegahan penularan Covid-19 yaitu dengan mengkonsumsi vitamin dan suplemen kesehatan. Kata Kunci: Stress Kerja Antara Perawat UGD Dan Ruang Rawat Inap